Uncovering a Functional Motif of Nonlinear Optical Materials by In Situ Electron Density and Wavefunction Studies Under Laser Irradiation - Jiang, Xiao‐Ming; Lin, Shu‐Juan; He, Chao; Liu, Bin‐Wen; Guo, Guo‐Cong (Angewandte Chemie International Edition, 2021)
Exploring nonlinear optical (NLO) functional motifs (FM, the structural origin of NLO efficiency) is vital for the rational design of NLO materials. Normal spectrum techniques applied in studying photon exciting materials are invalid for NLO materials, in which electrons are not excited substantially but only distorted under laser. A general strategy of determining NLO FM is proposed by comparative studies of experimental electron density (ED) without and under the laser. The in situ experimental ED and wavefunction of typical NLO material LiB3O5 (LBO) under dark and 360 and 1064 nm lasers are investigated. Compared with the initial state under dark, the ED of [B3O5]− unit at functional states under laser irradiation exhibits remarkable changes of topological atomic and bond properties, confirming the NLO FM being [B3O5]−. The work extracts for the first time the FM of a NLO material experimentally and highlights the crucial role of in situ ED analysis in studying NLO mechanisms. A general strategy of determining nonlinear optical (NLO) functional motif (FM) is proposed by comparative studies of experimental electron density (ED) without and under the laser. In situ ED analysis is firstly adopted for an NLO material with typical LiB3O5 as an example. The work extracts the FM of a NLO material experimentally and highlights the crucial role of in situ ED analysis in studying NLO mechanisms.